Photoreceptor control of Platynereis growth and lifespan via evolutionarily conserved molecular pathways - Gabriele Andreatta; Federico Scaramuzza; Aida Ćorić; Lukas Orel; Audrey M. Mat; Hiroki Takekata; Birgit Poehn; Nadja Milivojev; Kristin Tessmar-Raible (Proceedings of the National Academy of Sciences, 2026)
Natural light is severely affected by human impact on Earth, yet little is known about the roles light receptors have outside vision and rhythmic processes, despite their tremendously wide abundance. Here we show that loss-of-function of the light-receptive cryptochrome ( l-cry ) in marine bristleworms significantly increases lifespan and adult size, similarly to wild-types reared in constant darkness. Quantitative transcriptomics revealed hormonal players crucial for invertebrate and vertebrate sexual development and reproduction affected in l-cry mutants. These include nr0b1/2 , ortholog of dax-1 ( nr0b1 ) and shp ( nr0b2 ), long considered vertebrate novelties. Depending on moon-phase, nr0b1/2 is up- or down-regulated in l-cry mutants. Matching the complex regulation, data consistent with loss of nr0b1/2 function partially recapitulate l-cry phenotypes. Molecularly, Platynereis Nr0b1/2 affects steroidogenic and other endocrine pathways, nuclear receptor signaling, and transcription factor orthologs involved in sexual developmental, reproductive, and timing processes in other organisms. Thus, our study suggests profound and direct effects of light on adult animal life-time, likely at least in part via conserved endocrine pathways involved in sexual maturation and reproduction in annelids and vertebrates.